Enhancement of microwave ring resonator based on poly-lactic acid thermoplastic substrate - Nurul Hanani Manab; Elfarizanis Baharudin; Fauziahanim Che Seman; Rosnah Mohd. Zin (Institute of Advanced Engineering and Science, 2020)
In this paper, the development of a single-port microwave ring resonator (MRR) sensor based on a thermoplastic material, which is poly-lactic acid (PLA), is presented. The open-ended coaxial probe method was applied to identify the dielectric properties of PLA in terms of dielectric constant (2.25) and loss tangent (0.0001). The PLA substrate was fabricated using a hot press machine and with the same thickness (1.6 mm) as FR4. Hence, to consider the PLA as microwave substrate, microwave ring resonator (MRR) operating at 1.1 GHz resonance frequency was designed, simulated, and measured. Based on the observation, the return loss of MRR for the simulation and the measurement of the conventional design are -5.37 dB and -5.02 dB, respectively. The quality factor (Q-factor) for both are 122.22 and 183.33, respectively. Then, the enhanced coupling gap method was applied to improve the performance of MRR sensitivity in terms of return loss and Q-factor. It is observed that the return loss of the enhanced design for the simulation and the measurement are -26.67 dB and -20.23 dB, respectively, and the Q-factor are 122.22 and 200, respectively. Thus, the performance of the MRR based on different designs were compared in order to validate the sensor’s sensitivity and PLA can be recognized as a substrate material for RF and microwave applications.